From Religious Harmony Forum to Multicultural Da'wah Agency: Da'wah Syuubiyah wa Qabailiyah and Social Cohesion - Syamsuddin; Dindin Solahudin; Ridwan Rustandi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2026)
Indonesia’s religious and cultural plurality requires a da'wah paradigm that can transform diversity into social cohesion. This need becomes more urgent amid local religious tensions, digital sectarian narratives, and the growing demand for institutional mediation. However, studies on the Forum for Religious Harmony (FKUB) mostly examine it as a state-supported harmony forum. They rarely analyze FKUB as a multicultural da'wah agency that operates da'wah syuubiyah wa qabailiyah. This study aims to reconstruct the operational paradigm of da'wah syuubiyah wa qabailiyah practiced by FKUB Bandung Regency. It also evaluates its models, strategies, and contributions to social cohesion. This study employed a qualitative single-case study design. Data were collected through participatory observation, in-depth interviews with twelve informants, and analysis of FKUB program documents. The data were analyzed using thematic analysis through data condensation, data display, and conclusion verification. The findings show that FKUB Bandung Regency develops three interrelated models of da'wah syuubiyah wa qabailiyah. These are a dialogical model rooted in Sundanese local wisdom, a community-based empowerment model through moderation agents, and a multi-stakeholder collaborative model. These models strengthen social cohesion through conflict prevention, bridging social capital, inclusive national identity, and counter-narratives to extremism. The study contributes to Islamic Da'wah Science by extending da'wah syuubiyah wa qabailiyah from a normative concept into an institutional and sociological framework for multicultural da'wah in Indonesia’s plural democracy.